SENTIMENT ANALYSIS OF TWITTER (X) RESPONSES USING NAÏVE BAYES: A CASE STUDY OF JUMBO: SENTIMENT ANALYSIS - Nurasiah; Latifah Nur Zam Zami; Yunianto Agung Nugroho (LPPM Nusa Mandiri, 2026)
The rapid growth of social media platforms, especially Twitter (now rebranded as X), has made it a rich source for public opinion mining. This study focuses on analyzing public sentiment toward the animated “film Jumbo